Improved Virtual Planning for Bimaxillary Orthognathic Surgery. Issue 6 (September 2016) - Hatamleh, Muhanad; Turner, Catherine; Bhamrah, Gurprit; Mack, Gavin; Osher, Jonas
Abstract : Abstract: Conventional model surgery planning for bimaxillary orthognathic surgery can be laborious, time-consuming and may contain potential errors; hence three-dimensional (3D) virtual orthognathic planning has been proven to be an efficient, reliable, and cost-effective alternative. In this report, the 3D planning is described for a patient presenting with a Class III incisor relationship on a Skeletal III base with pan facial asymmetry complicated by reverse overjet and anterior open bite. A combined scan data of direct cone beam computer tomography and indirect dental scan were used in the planning. Additionally, a new method of establishing optimum intercuspation by scanning dental casts in final occlusion and positioning it to the composite-scans model was shown. Furthermore, conventional model surgery planning was carried out following in-house protocol. Intermediate and final intermaxillary splints were produced following the conventional method and 3D printing. Three-dimensional planning showed great accuracy and treatment outcome and reduced laboratory time in comparison with the conventional method. Establishing the final dental occlusion on casts and integrating it in final 3D planning enabled us to achieve the best possible intercuspation.